Identity Verification Using Zero-Knowledge-Proof With Blockchain Technology - Shyni, S. Adolphine; priyan, E Vishnu; V Ilavarasan, V Ilavarasan; B Nithyanadhan, B Nithyanadhan; M Ranjith, M Ranjith (Journal of Neonatal Surgery, 2025)
The Demand for privacy preserving, identity management systems has been escalating dramatically in recent years. To meet this valid need, innovative solutions are required to manage data integrity, user privacy, and access to government services. This paper develops a government identity management system based on blockchain and zero knowledge proofs which allows users to be authenticated without revealing any sensitive information. The proposed architecture incorporates biometric verification, government verification APIs and decentralized storage along with ZKP to enhance security. Identifiable credentials are proved without revealing the actual data through ZKP authentication, while blockchain serves the purpose of record keeping. Several performance metrics such as response time, encryption time, transaction time, and user satisfaction levels has proven the efficiency and scalability of the system. The system from the comparative analysis showed how the wider systems lack in the preservation of privacy, integrity, and transparency and how these issues were solved. The striking features of the system include practical solutions to the long-standing latency, computational overheads, and compliance security concerns as they relate to modern identity management systems in government applications .